Peculiarities of regional development and management processes at present stage - S. K. Khamirzova; A. R. Kumpilova (Новые технологии, 2017)
The article considers features of regional development and management as a reproduction process in the regional socio-economic system; it is pointed out that regional development should be aimed at achieving strategic goals and is conditioned by the resource provision, as well as the impact of a combination of internal and external factors.